Identity Styles and High-Risk Behaviors in Adolescence: Evolution from Early to Late Stages - Imani Khoshkhoo, Shahin; Rezaei, Sajjad; Hosseinkhanzadeh, Abbas Ali (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2026)
Objective: Adolescence involves rapid physical, psychological, and social changes that can increase engagement in high-risk behaviors. Investigating the role of identity styles in these behaviors may aid in developing effective prevention and intervention strategies for adolescents. Methods and Materials: This cross-sectional study examined male middle and high school students in Siahkal County, Iran, during the 2023-2024 academic year. The sample included 435 students aged 11 to 19, divided equally across three groups representing early, middle, and late adolescence. Data were collected via surveys using Berzonsky’s Identity Style Inventory (1989) and the Iranian Adolescent Risk-Taking Scale (2011). Statistical analyses included Pearson correlation, multiple linear regression, and Fisher’s Z-test. Findings: Distinct patterns emerged between identity styles and high-risk behaviors across adolescence. The normative identity style was consistently associated with reduced high-risk behaviors, with the strongest protective effects observed during late adolescence (p < 0.01). The diffuse-avoidant identity style correlated with increased engagement in high-risk behaviors across all stages of adolescence (p < 0.01), particularly in late adolescence, where a pronounced tendency toward opposite-sex interactions was observed (z > 1.96). The informational identity style demonstrated a significant protective role, especially in late adolescence (p < 0.01), effectively reducing tendencies toward alcohol use. Conclusion: These findings indicate that distinct identity styles have significant and varying associations with high-risk behaviors throughout adolescence. The results support the design of targeted and predictive interventions and support programs tailored to each identity style and developmental stage to reduce high-risk behaviors.